The efficacy of using a holistic 4-domain approach in evaluating frailty in ambulatory patient with heart failure. (14th October 2021) - Sze, S; Pellicori, P; Zhang, J; Weston, J; Squire, I B; Clark, A L
Abstract: Background: Recently, the Heart Failure Association (HFA) of the European Society of Cardiology (ESC) proposed a four-domain approach to assess frailty in patients with heart failure (HF), to tailor treatment and potentially improve outcomes. The efficacy of such approach in detecting frailty and predicting outcome in patients with HF is unknown. Aim: To study the prevalence and prognostic value of four different types of frailty deficits: clinical, physical, cognitive and social frailty in ambulatory patients with HF. Methods: We assessed prospectively consecutive patients attending a routine follow-up visit. Patients with ≥5 non-HF comorbidities were classified as having a clinical deficit. Those who scored ≥3 using the Fried criteria were classified as having a physical deficit. Those who failed to complete a clock test accurately were classified as having a cognitive deficit. Those who lived alone or in a residential home were classified as having a social deficit. All patients were followed for a minimum of 1 year. The primary end point is all-cause mortality. Results: We enrolled 467 patients (67% male, median (25th–75th centile) age 76 (69–82) years, median (25th–75th centile) NT-proBNP 1156 (469–2463) ng/L). 65% of patients had clinical deficits, 52% had a physical deficit, 39% had a social deficit and 18% had a cognitive deficit. 28% had 2, 19% had 3, 8% of patients had all 4 deficits; 16% had none. An increasing number of frailty deficits was associated with worse symptoms, higher NT-proBNP and less likelihood of being prescribed guideline-indicated HF treatment. During a median follow-up of 554 days, 82 patients died. The presence of any frailty deficit was associated with increased risk of mortality. (Figure 1) The more frailty deficit a patient had, the higher the risk of mortality (Figure 2). A base model (including age, body mass index, NYHA class and log [NT-proBNP]) for predicting mortality at 1 year achieved a C-statistic of 0.78. Addition of all four deficits improved the performance of the base model (C-statistic = 0.82). Conclusion: Clinical, physical, cognitive and social deficits are common in patients with HF and are associated with a poor outcome. Future studies should evaluate how a domain-based approach can be used to optimise care for frail patients with HF. Funding Acknowledgement: Type of funding sources: None.